Konstruk Estetika Hindu dalam Realitas Seni di Bali - Danu Tirta, I Made (Universitas Hindu Negeri I Gusti Bagus Sugriwa Denpasar, 2019)
Construction of Hindu aesthetics has always been the axis and soul towards the reality of artistic life in Bali. The basic principles of Hindu aesthetics are applied in a good and consistent manner in structuring the life of art, so that a balance is created in every work of art produced. Every aspect of life of the Balinese people always emphasizes this aesthetic aspect so that they not only give birth to works of art, but also their life’s journey looks aesthetic. Narratively, this paper tries to give a simple review of aesthetic concepts in Hinduism, which is then synergized into several basic principles or theorems of Hindu society and Balinese art activists, in realizing various classifications of works and spirit of art in Bali. The six absolute classifications (Sad Angga) in Hindu aesthetics must form the basis for the artists to create works of art that focus on the principles of chastity, truth and beauty. So that, when it is implemented in Balinese arts, then forms of works and art activities appear that are religious and Metaksu nuances. This is an interesting order to be observed and passed on by the next generation